Bortezomib, C1‐Inhibitor and Plasma Exchange Do Not Prolong the Survival of Multi‐Transgenic GalT‐KO Pig Kidney Xenografts in Baboons. Issue 2 (February 2015) - Le Bas‐Bernardet, S.; Tillou, X.; Branchereau, J.; Dilek, N.; Poirier, N.; Châtelais, M.; Charreau, B.; Minault, D.; Hervouet, J.; Renaudin, K.; Crossan, C.; Scobie, L.; et al.
<x xml:space="preserve">Abstract</x> Galactosyl‐transferase KO (GalT‐KO) pigs represent a potential solution to xenograft rejection, particularly in the context of additional genetic modifications. We have performed life supporting kidney xenotransplantation into baboons utilizing GalT‐KO pigs transgenic for human CD55/CD59/CD39/HT. Baboons received tacrolimus, mycophenolate mofetil, corticosteroids and recombinant human C1 inhibitor combined with cyclophosphamide or bortezomib with or without 2–3 plasma exchanges. One baboon received a control GalT‐KO xenograft with the latter immunosuppression. All immunosuppressed baboons rejected the xenografts between days 9 and 15 with signs of acute humoral rejection, in contrast to untreated controls (n = 2) that lost their grafts on days 3 and 4. Immunofluorescence analyses showed deposition of IgM, C3, C5b‐9 in rejected grafts, without C4d staining, indicating classical complement pathway blockade but alternate pathway activation. Moreover, rejected organs exhibited predominantly monocyte/macrophage infiltration with minimal lymphocyte representation. None of the recipients showed any signs of porcine endogenous retrovirus transmission but some showed evidence of porcine cytomegalovirus (PCMV) replication within the xenografts. Our work indicates that the addition of bortezomib and plasma exchange to the immunosuppressive regimen did not significantly prolong the survival of multi‐transgenic GalT‐KO renal xenografts. Non‐Gal antibodies, the alternative complement pathway, innate mechanisms with monocyte activation and PCMV replication may have contributed to rejection.